Complexity-Aware Quantization and Lightweight VLSI Implementation of FIR Filters. (12th January 2011) - Kuo, Yu-Ting; Lin, Tay-Jyi; Liu, Chih-Wei
Abstract : The coefficient values and number representations of digital FIR filters have significant impacts on the complexity of their VLSI realizations and thus on the system cost and performance. So, making a good tradeoff between implementation costs and quantization errors is essential for designing optimal FIR filters. This paper presents our complexity-aware quantization framework of FIR filters, which allows the explicit tradeoffs between the hardware complexity and quantization error to facilitate FIR filter design exploration. A new common subexpression sharing method and systematic bit-serialization are also proposed for lightweight VLSI implementations. In our experiments, the proposed framework saves 49% 51% additions of the filters with 2's complement coefficients and 10% 20% of those with conventional signed-digit representations for comparable quantization errors. Moreover, the bit-serialization can reduce 33% 35% silicon area for less timing-critical applications.